In-vitro cytocidal effect of water on bladder cancer cells: The potential role for intraperitoneal lavage during radical cystectomy - Taoka, Rikiya; Williams, Stephen B.; Ho, Philip L.; Kamat, Ashish M. (Canadian Urological Association Journal, 2015)
Introduction: We investigate the cytocidal effect of water on bladder cancer cells. Intraperitoneal lavage with sterile water is sometimes used during radical cystectomy to lyse cancer cells that might have escaped the surgical specimen. The efficacy of this approach at the cellular level is unknown. Methods: Three bladder cancer cell lines of varying grade, RT4, TCCSUP and T24 were exposed to sterile water, and morphological changes were closely observed under microscopy. Changes of cell membrane integrity, cell viability, and cell number of reincubated cells after water exposure were measured to determine water induced hypotonic shock. Results: The low-grade RT4 cells started swelling immediately upon exposure to water followed by rupture within 3 minutes. The higher grade TCCSUP and T24 cells demonstrated limited hypotonic swelling with significantly less cell rupture after 10 minutes. The damage to cell membrane of RT4 cells was evident at 1 minute; only 10.0% of cells were intact at 10 minutes. On the other hand, 41.9% and 77.8% of TCCSUP and T24 cells were intact at 10 minutes, respectively. Percentage of viable cells at 10 minutes was 2.1 ± 2.3%, 2.3 ± 0.4%, and 16.1 ± 0.6% for RT4, TCCSUP, and T24, respectively. Conclusions: Cytocidal effect of hypotonic shock can be achieved, to varying degrees, by exposing bladder cancer cells to water for at least 10 minutes. This in vitro study may have bearing on the effects seen with intraperitoneal lavage using sterile water during radical cystectomy.